2017
DOI: 10.24171/j.phrp.2017.8.6.09
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiviral Activity of Sakuranetin against Human Rhinovirus 3

Abstract: ObjectivesRhinoviruses (RVs) cause common cold and are associated with exacerbation of chronic inflammatory respiratory diseases. Until now, no clinically effective antiviral chemotherapeutic agents to treat diseases caused by human rhinoviruses (HRVs) have been reported. We assessed the anti-HRV3 activity of sakuranetin isolated from Sorbus commixta Hedl. in human epithelioid carcinoma cervix (HeLa) cells, to evaluate its anti-rhinoviral potential in the clinical setting.MethodsAntiviral activity and cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Furthermore, entry of rhinovirus was shown to be inhibited in silico by inhibition of the protein grid of virus [61]. Another flavonoid sakuranetin was also identified as a potent inhibitor of rhinovirus-3 by its antioxidant properties [62]. Several other flavonoids were reported to inhibit the activity of various picornaviruses [60,[63][64][65][66].…”
Section: Flavonoids Against Non-ev-a71 Picornavirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, entry of rhinovirus was shown to be inhibited in silico by inhibition of the protein grid of virus [61]. Another flavonoid sakuranetin was also identified as a potent inhibitor of rhinovirus-3 by its antioxidant properties [62]. Several other flavonoids were reported to inhibit the activity of various picornaviruses [60,[63][64][65][66].…”
Section: Flavonoids Against Non-ev-a71 Picornavirusesmentioning
confidence: 99%
“…In vitro Replication Antioxidant activity through inhibition of viral adsorption [62] Structures of flavonoids are provided in Supplementary Materials Table S1.…”
Section: Hrv-3mentioning
confidence: 99%
“…In our experiments, sakuranetin was shown to exhibit anti‐influenza B/Lee/40 virus activity against influenza B/Lee/40 virus, reducing the formation of a visible CPE (Choi, ). Several previous reports have documented that flavonoids possess antiviral activities against human immunodeficiency virus, hepatitis B virus, and human rhinovirus 3 (Choi, ; Choi, Bae, Song, Baek, & Kwon, ; Choi, Song, et al, ). These properties are attributed to the antiviral activity of flavonoids.…”
Section: Resultsmentioning
confidence: 93%
“…A literature search on sakuranetin showed that sakuranetin inhibits chemically induced edema in mice and alleviates the allergen‐induced lung injury model through control of NF‐κB (Hernández, Recio, Máñez, Giner, & Ríos, ; Toledo et al, ). In our study, sakuranetin showed anti‐human rhinovirus 3 activity in vitro (Choi, ). However, to date, antiviral effects of sakuranetin against influenza B virus have not been reported.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation